2006
DOI: 10.1086/503056
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Traits Determine the Growth‐Survival Trade‐Off across Rain Forest Tree Species

Abstract: A dominant hypothesis explaining tree species coexistence in tropical forest is that trade-offs in characters allow species to adapt to different light environments, but tests for this hypothesis are scarce. This study is the first that uses a theoretical plant growth model to link leaf trade-offs to whole-plant performances and to differential performances across species in different light environments. Using data of 50 sympatric tree species from a Bolivian rain forest, we observed that specific leaf area an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
190
2
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(220 citation statements)
references
References 26 publications
24
190
2
4
Order By: Relevance
“…However, these early studies focussed mostly on visual symptoms and did not report quantitative data suitable for meta-analysis. The observed decrease in the proportion of studies conducted in these regions corresponds well to the decline in emissions following changes in industrial practices and the introduction of emission controls (Cape et al 2003;Stern 2006). The increase in the number of studies originating from Russia and the Ukraine in the 1990s was associated with the removal of governmental restrictions concerning publication of ''negative'' environmental information.…”
Section: Spatial and Temporal Trends In Pollution Researchmentioning
confidence: 83%
See 2 more Smart Citations
“…However, these early studies focussed mostly on visual symptoms and did not report quantitative data suitable for meta-analysis. The observed decrease in the proportion of studies conducted in these regions corresponds well to the decline in emissions following changes in industrial practices and the introduction of emission controls (Cape et al 2003;Stern 2006). The increase in the number of studies originating from Russia and the Ukraine in the 1990s was associated with the removal of governmental restrictions concerning publication of ''negative'' environmental information.…”
Section: Spatial and Temporal Trends In Pollution Researchmentioning
confidence: 83%
“…Although environmental pollution is an integral part of global change (Taylor et al 1994), a vast majority of the research addressing the biotic effects of global change overlooks this issue (but see, e.g., Settele et al 2005). The synthesis of existing knowledge on changes in plant growth and reproduction near industrial enterprises contributes to the integration of pollution ecology and global change research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When and where resources are more available, species with trait values associated with resource acquisition are expected to perform better, while those with trait values associated with resource conservation exhibit better performance where resources are limiting (Rees et al 2001;Reich 2014). For example, Sterck et al (2006) found that high specific leaf area (SLA), photosynthesis rates, and leaf N content facilitated faster growth in forest gaps and that species with long-lived leaves and low SLA had higher survival rates under a closed canopy. However, not all functional traits or trait syndromes explain variation in ecological processes equally well (Lasky et al 2013Wright et al 2010).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Where species occur along this axis is strongly governed by the partitioning of resource gradients, principally light Sterck et al 2006Sterck et al , 2011Wright et al 2010), as well as soil nutrients (Russo et al 2008). Consequently, species-specific adaptations to Abstract Adaptations to resource availability strongly shape patterns of community composition along successional gradients in environmental conditions.…”
Section: Introductionmentioning
confidence: 99%